2018
DOI: 10.1002/dvdy.24637
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to study coronary vasculature development in mice

Abstract: The techniques described here enable us to study the finer details of coronary artery development in mice and can, therefore, be implemented to study the pathogenesis of coronary malformations in various mouse models. Developmental Dynamics 247:1018-1027, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
0
18
0
5
Order By: Relevance
“…Although there are limited studies on the coronary anatomy of murine hearts, which is slightly different from that of humans’, it has been shown that C57BL/6J mice have three main coronaries and that their coronary arteries are intramyocardial rather than epicardial as in humans. In these mice, the left, right and septal coronary arteries (the septal artery may originate from either the left or right coronary, or two septal coronaries may coexist from either 33 ) supply the left and right ventricles, and interventricular septum, respectively 33 36 . Thus, SAC-induced hypertensive heart disease predominantly involves collagen deposition, due to fibroblast proliferation 32 , around the arteries branching from the left coronary artery into the LV free wall 34 , 36 rather than from those located in the interventricular septum (IVS), perhaps indicating greater wall stress due to a higher transmural pressure in the LV free wall than that across the IVS.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited studies on the coronary anatomy of murine hearts, which is slightly different from that of humans’, it has been shown that C57BL/6J mice have three main coronaries and that their coronary arteries are intramyocardial rather than epicardial as in humans. In these mice, the left, right and septal coronary arteries (the septal artery may originate from either the left or right coronary, or two septal coronaries may coexist from either 33 ) supply the left and right ventricles, and interventricular septum, respectively 33 36 . Thus, SAC-induced hypertensive heart disease predominantly involves collagen deposition, due to fibroblast proliferation 32 , around the arteries branching from the left coronary artery into the LV free wall 34 , 36 rather than from those located in the interventricular septum (IVS), perhaps indicating greater wall stress due to a higher transmural pressure in the LV free wall than that across the IVS.…”
Section: Discussionmentioning
confidence: 99%
“…Hearts perfused with polymerized yellow Microfil (Flow Tech) were prepared as described previously (69) and processed by micro-CT scanning (SkyScan 1272; Bruker). Projection images were reconstructed using NRecon SW (Bruker).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, this group also performed TEM analysis, which revealed that BABB‐treated heart integrity is severely compromised, when compared with much less extensive deformation observed in CUBIC‐treated samples . Transparency achievable in Sca l e treated samples, although too low for imaging of adult hearts, is sufficient to study murine hearts at early stages of the embryonic development. As such, application of Sca l e by Li et al .…”
Section: Application Of Toc For Particular Peripheral Organsmentioning
confidence: 99%